THE REFLECTION OF THE ARTICLE 8 OF THE EUROPEAN CONVENTION ON HUMAN RIGHTS IN THE ROMANIAN LAW IN FORCE, INTO THE LIGHT OF THE E.C.H.R. JURISPRUDENCE - Dan, Lutescu; Catalin, Bucur (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
The following article intends to show how the article 8 of the European Convention on Human Rights, concerning the right to respect for private life, finds its reflection in the Romanian law in force. Starting from the interpretation of the article 8 of the Convention, but also taking under consideration the official criteria for legal interpretation materialized in the jurisprudence of the European Court for Human Rights, the authors aim to identify the extent of the correlation of our national legislation, particularly the penal law, with the letter and the spirit of the Convention, in the matter debated. This study also includes an analysis of the Romanian law in force, with its most recent modifications and completions and the required comment on the subject of the legal interpretation that should be used. It is also considered the incidence of the constitutional principle of the preference of the international legal regulations to the national legislation, in the matter in question, aswell as the most effective way to interpret and enforce the Romanian legislation, without contravening the Convention. The reader will also find, within the study bellow, certain legal observations regarding the endless controversy aroused by the issue of the legitimacy and the legality of the disclosure, through the mass-media, of slanderous informations about public life persons, a true Pandora’s box in the Romanian society. Keywords: European Convention on Human Rights, right to respect for private life, European Court for Human Rights, national legislation, penal law